2017
DOI: 10.1016/j.celrep.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Determinants of Protein Abundance Variation in Colorectal Cancer Cells

Abstract: SummaryAssessing the impact of genomic alterations on protein networks is fundamental in identifying the mechanisms that shape cancer heterogeneity. We have used isobaric labeling to characterize the proteomic landscapes of 50 colorectal cancer cell lines and to decipher the functional consequences of somatic genomic variants. The robust quantification of over 9,000 proteins and 11,000 phosphopeptides on average enabled the de novo construction of a functional protein correlation network, which ultimately expo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
182
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(197 citation statements)
references
References 55 publications
(73 reference statements)
15
182
0
Order By: Relevance
“…This genetic dissection has revealed that NuRD component proteins display a large degree of inter-dependence for protein stability, as has been reported for other multiprotein complexes (Roumeliotis et al, 2017). Mta1 and Mta2 both contain two distinct RBBP interaction domains, while Mta3 lacks the C-terminal most RBBP interaction domain (Millard et al, 2016).…”
Section: Discussionsupporting
confidence: 60%
“…This genetic dissection has revealed that NuRD component proteins display a large degree of inter-dependence for protein stability, as has been reported for other multiprotein complexes (Roumeliotis et al, 2017). Mta1 and Mta2 both contain two distinct RBBP interaction domains, while Mta3 lacks the C-terminal most RBBP interaction domain (Millard et al, 2016).…”
Section: Discussionsupporting
confidence: 60%
“…Zhang et al, 2014) . In addition we compiled existing protein/gene expression and copy-number data for cancer cell lines from Lapek et al (BRCA) (Lapek et al, 2017) , Roumeliotis et al (COREAD) (Roumeliotis et al, 2017) and Lawrence et al (BRCA) (Lawrence et al, 2015) . In total, 368 cancer samples (294 tumours and 74 cell lines) were compiled in our study with matched gene expression, copy-number and protein abundance ( Figure 1A ).…”
Section: Protein Level Attenuation Of Gene Dosage Associates With Dismentioning
confidence: 99%
“…These results are in-line with pulse chase degradation measurements showing that several complex subunits have a two-state degradation profile, that is compatible with a model in which they are expressed above the required levels and have a higher degradation rate when unbound from the complex (McShane et al, 2016) . The attenuation of changes at the protein level also justifies why protein complex subunits show higher correlation of protein abundances than the corresponding mRNA levels (Ryan, Kennedy, Bajrami, Matallanas, & Lord, 2017;Wang et al, 2017) and why correlation analysis can be used to identify cancer specific interaction networks (Lapek et al, 2017;Roumeliotis et al, 2017) .…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry (MS) is the main proteomics technology, capable of providing systemwide measurements of protein expression, post-translational modifications and/or protein-protein interactions, among other pieces of information 7,8 . Accordingly, cancer cell lines proteomes have been characterised in a number of MS-based studies [9][10][11][12][13][14][15][16][17] . However, due to technological limitations, these and other currently publicly available proteomics datasets are usually smaller in scope in comparison to analogous genomics and transcriptomics studies.…”
Section: Introductionmentioning
confidence: 99%